01b. Mean of sample variance

01b. Mean of sample variance - Proof that mean value of s...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon
Proof that mean value of equals Mean value of (1) 2 s 2 σ - - = 1 2 2 2 n X n X E s i ( 29 ( 29 [ ] - - = 2 2 1 1 X nE X E n i
Background image of page 1

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full Document Right Arrow Icon
Recall that for the population Variance of X = Then for the sample Variance of So, ( 29 ( 29 2 2 2 2 μ σ - = - = X E X E ( 29 2 2 2 - = = X E n X ( 29 ( 29 2 2 2 2 2 2 + = + = n X E X E
Background image of page 2
Substituting in equation (1), we get Mean value of Hence, mean value of ( 29
Background image of page 3
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}

Page1 / 3

01b. Mean of sample variance - Proof that mean value of s...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online